Impact of an abbreviated protocol for breast MRI in diagnostic accuracy - Guillaume Oldrini; Imad Derraz; Julia Salleron; Frédéric Marchal; Philippe Henrot (Diagnostic and Interventional Radiology, 2018)

(untitled)
PURPOSE:We aimed to compare the diagnostic accuracy and interpretation time of an abbreviated protocol relative to the complete protocol of breast magnetic resonance imaging (MRI) with the use of breast imaging reporting and data system (BI-RADS). Between-reader and between-protocol variability for BI-RADS classification and influence of reader expertise on diagnostic accuracies were also evaluated.METHODS:We conducted a retrospective reader study in 90 women who underwent breast MRI: 30 benign examinations (graded as American College of Radiology [ACR] 1 or 2), 30 examinations graded as ACR 3 and 30 examinations requiring a histologic proof (graded as ACR 4 or 5). Two radiologists independently reviewed the protocols. The reference standard was 24 months of imaging follow-up (66.6%, n=60), percutaneous biopsy at the12th month imaging follow-up (5.5%, n=5), and breast surgery (27.9%, n=25). Analysis was done on a per-breast basis. There were 26 cancers in 168 breasts (15.1%)RESULTS:Interpretation time was higher for the complete protocol (mean difference: 84 s, 95% CI [67;101] for senior and 83 s, 95% CI [70;95] for junior reader; P < 0.001). The reliability of BI-RADS classification between both protocols was very good with intraclass correlation coefficient of 0.89 for junior reader and 0.98 for senior reader; the inter-reader reliability was 0.94 and 0.90 for the complete and abbreviated protocols, respectively. For senior reader, the abbreviated and complete protocols yielded 95.1% and 94.4% specificity and 100% sensitivity.CONCLUSION:Our data provide corroborating evidence that abbreviated protocols decrease interpretation time without compromising sensitivity or specificity. There was a high level of concordance between the abbreviated and complete protocols and between the two readers.